2016
DOI: 10.4049/jimmunol.1502184
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Target Sequences and Repair Pathways Determines Distinct Outcomes of AID-Initiated Lesions

Abstract: Activation-induced deaminase (AID) functions by deaminating cytosines and causing U:G mismatches, a rate-limiting step of antibody gene diversification. However, precise mechanisms regulating AID-deamination frequency remain incompletely understood. Moreover, it is unknown whether different sequence contexts influence the preferential access of mismatch repair (MMR) or uracil glycosylase (UNG) to AID-initiated U:G mismatches. Here, we employed two knock-in models to directly compare the mutability of core Sµ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 54 publications
(77 reference statements)
0
11
1
Order By: Relevance
“…In remarkable convergence with this footprint size, Woodrick et al (46) showed that LP-BER produces excision patches centered on the excised AP site that are ≤20 nucleotides long; they further showed that LP-BER predominates over single-nucleotide BER in living cells. AGCW motifs are the only hotspots where AID can deaminate either DNA strand with comparable efficiency in vivo (8,9,47). This leads us to update the Ig hypermutation model and propose that MMR-independent C/G transversions occur via simultaneous G 1 -phase LP-BER of deaminations that have accumulated in Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In remarkable convergence with this footprint size, Woodrick et al (46) showed that LP-BER produces excision patches centered on the excised AP site that are ≤20 nucleotides long; they further showed that LP-BER predominates over single-nucleotide BER in living cells. AGCW motifs are the only hotspots where AID can deaminate either DNA strand with comparable efficiency in vivo (8,9,47). This leads us to update the Ig hypermutation model and propose that MMR-independent C/G transversions occur via simultaneous G 1 -phase LP-BER of deaminations that have accumulated in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…S1), presumably by the U:G mismatches deamination induces. Processing via BER or MMR predominantly restores C in place of U (6)(7)(8)(9) but is also error-prone. Error-prone BER converts deamination sites into transition or transversion mutations at C/G and occasionally produces mutations at bases flanking deamination sites, including A/T bases (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of UNG2 activity can also increase the frequency of C:G to T:A transition mutations, presumably as a result of increased uracil replication. This suggests that high fidelity uracil BER does occur in hypermutating B cells ( 9 , 11 , 19 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the mouse Sμ switch region contains a high density of AGCT hotspots, this density varies within the switch region, which led the authors to define sub-regions reflecting sparse, intermediate and dense AGCT densities. Interestingly, across the sub-regions mutation frequency did not correlate with AGCT density, suggesting that AID targeting is efficient once a threshold density is reached, and that higher densities do not necessarily increase the mutation targeting frequency [ 42 ].…”
Section: Discussionmentioning
confidence: 99%